Effectiveness, safety, and tolerability of delayed dexamethasone, rituximab, and cyclophosphamide as first-line treatment in patients with Waldenström macroglobulinemia: data from the Sicilian Myeloma Network - Vittorio Del Fabro; Uros Markovic; Sara Frazzetto; Sara Frazzetto; Roberta Sciortino; Claudia Bellofiore; Mary Ann Di Giorgio; Valerio Leotta; Anna Bulla; Angelo Curto Pelle; Federica Elia; Donato Mannina; et al. (Frontiers in Hematology, 2024)
BackgroundWaldenström macroglobulinemia (WM) is a rare and indolent B-cell lymphoproliferative disorder with greater incidence in elderly patients where a precise algorithm of initial therapy is still not clear. Immunochemotherapy regimen consisting of dexamethasone, rituximab, and oral cyclophosphamide (DRC) is considered a suitable first-line treatment because of its safety, efficacy, and manageability.Patients and methodsWe retrospectively describe the results of 36 consecutive treatment-naïve patients with WM who were treated from June 2013 until June 2021 with the DRC regimen every 4 weeks instead of 3 weeks, for six cycles. The median age was 69 years (range, 42–85 years), with one-third being older than 75 years. Most patients had features of advanced disease, with nearly 60% being high risk. Median IgM level prior to treatment initiation was 2.9 g/dL.ResultsOverall response rate was 80% after a median time of two cycles, with 67% of patients achieving at least partial response. After a median follow-up of 59 months, the median overall survival (OS) was not reached and the median time to next treatment (TTNT) was 48 months (95% CI 25–87 months). Approximately 70% of the evaluable study population had a 3-year survival without additional treatment, while 75% had a 3-year OS rate. The treatment was well-tolerated with only two patients (6%) recorded to have grade 3 pneumonia and no grade 3 hematological toxicity maybe due to the regular use of growth factors for red and white blood cells. Baseline albumin level and achievement of at least minimal or partial response had a significant impact on TTNT, while baseline hemoglobin and IgA level affected outcome in terms of OS (p < 0.05).ConclusionThis is the first real-life experience describing the use of the DRC regimen in treatment-naive patients with WM with administration of therapy every 4 weeks instead of 3 weeks showing apparent comparable efficacy, along with good tolerability and safety, especially in terms of hematological toxicity, independently from comorbidity burden.